(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Some people will take advantage of this technology. One of them is to display himself or herself to attract somebody else. This research focused on how users communicate themselves via social media especially Tik Tok application. It’s fascinating to see how social media platforms have evolved into self-promotional platforms. Data were collected through interviews with Tik Tok users and observation. A communication theory that is relevant to analyse this issue is dramaturgy. The research result showed that Tik Tok is used for any kinds of purposes for users. One of them is for displaying him/herself for certain reasons. It is about playing role. What is displayed is different from the reality.